Effect of guanidine and arginine on protein–ligand interactions in multimodal cation‐exchange chromatography. (3rd February 2017) - Parimal, Siddharth; Garde, Shekhar; Cramer, Steven M.
Abstract : The addition of fluid phase modifiers provides significant opportunities for increasing the selectivity of multimodal chromatography. In order to optimize this selectivity, it is important to understand the fundamental interactions between proteins and these modifiers. To this end, molecular dynamics (MD) simulations were first performed to study the interactions of guanidine and arginine with three proteins. The simulation results showed that both guanidine and arginine interacted primarily with the negatively charged regions on the proteins and that these regions could be readily predicted using electrostatic potential maps. Protein surface characterization was then carried out using computationally efficient coarse‐grained techniques for a broader set of proteins which exhibited interesting chromatographic retention behavior upon the addition of these modifiers. It was shown that proteins exhibiting an increased retention in the presence of guanidine possessed hydrophobic regions adjacent to negatively charged regions on their surfaces. In contrast, proteins which exhibited a decreased binding in the presence of guanidine did not have hydrophobic regions adjacent to negatively charged patches. These results indicated that the effect of guanidine could be described as a combination of competitive binding, charge neutralization and increased hydrophobic interactions for certain proteins. In contrast, arginine resulted in a significant decrease in protein retention times primarily due to competition for the resin and steric effects, with minimal accompanying increase in hydrophobic interactions. The approach presented in this paper which employs MD simulations to guide the application of coarse‐grained approaches is expected to be extremely useful for methods development in downstream bioprocesses. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:435–447, 2017